The Usage of Islamic Financial Services in Zanzibar: The Influence of Accessibility, Relevancy and Expected Benefits - Moh’d Khamis, Fauz; Isa, Mohamad Yazid; Yusuff, Noraini (Everant Journals, 2022)
Aim: The study investigated the relationship between accessibility, relevance, expected benefits, and usage of Islamic financial services among Zanzibar residents. Method: This study was based on a quantitative approach. A multistage sampling process was used to obtain questionnaire responses across all five regions of Zanzibar. A total of 400 questionnaires were used for the analysis. Findings: The results indicate a significant influence of accessibility, relevancy, and expected benefits on the usage of Islamic financial services in Zanzibar. Limitation of the study: This study focuses on only three (supply-side) determinants of the use of Islamic financial services in Zanzibar. Practical Implication: This study provides empirical evidence in the new environment of Zanzibar, where Islamic finance is growing steadily. These findings will be useful for future researchers studying Islamic finance and financial inclusion. In addition, the study's findings provide research inputs to financial service providers and policymakers toward enhancing their reach to customers. Originality: This study is the first to assess the relationship between accessibility, relevance, expected benefits, and usage of Islamic financial services. In addition, the current study provides the evidence about usage of Islamic financial services in new environment; Zanzibar, the emerging Islamic financial market in East Africa